FAM83A and FAM83B: candidate oncogenes and TKI resistance mediators - Grant, Steven (American Society for Clinical Investigation, 2012)
The growth and survival of tumor cells can depend upon the expression of a single oncogene, and therapeutically targeting this oncogene addiction has already proven to be an effective approach in fighting cancer. However, it is also clear that cancer cells can adapt and become resistant to therapy through compensatory activation of downstream pathways that relieve the cell of its addicted phenotype. In this issue of the JCI, two groups — Lee et al. and Cipriano et al. — identify two related candidate oncogenes that might both contribute to therapeutic resistance to tyrosine kinase inhibitors (TKIs). If validated, this information could help to identify new targets for therapeutic interventions in breast cancer and possibly other cancers and may also assist in the development of strategies designed to overcome resistance to currently available TKIs.